Electrocardiographic Assessment and Genetic Analysis in Neonates: a Current Topic of Discussion - Sarquella-Brugada, Georgia; Cesar, Sergi; Zambrano, Maria D.; Fernandez-Falgueras, Anna; Fiol, Victoria; Iglesias, Anna; Torres, Francesc; Garcia-Algar, Oscar; Arbelo, Elena; Brugada, Josep; Brugada, Ramon; Campuzano, Oscar (Current Cardiology Reviews, 2019)
Background: Sudden death of a newborn is a rare entity, which may be caused by genetic cardiac arrhythmias. Among these diseases, Long QT syndrome is the most prevalent arrhythmia in neonates, but other diseases such as Brugada syndrome, Short QT syndrome and Catecholaminergic Polymorphic Ventricular Tachycardia also cause sudden death in infants. All these entities are characterized by well-known alterations in the electrocardiogram and the first symptom of the disease may be an unexpected death. Despite the low prevalence of these diseases, the performance of an electrocardiogram in the first hours or days after birth could help identify these electrical disruptions and adopt preventive measures. In recent years, there has been an important impulse by some experts in the scientific community towards the initiation of a newborn electrocardiogram-screening program, for the detection of these electrocardiographic abnormalities. In addition, the use of genetic analysis in neonates could identify the cause of these heart alterations. Identification of relatives carrying the genetic alteration associated with the disease allows adoption of measures to prevent lethal episodes. Conclusion: Recent technological advances enable a comprehensive genetic screening of a large number of genes in a cost-effective way. However, the interpretation of genetic data and its translation into clinical practice are the main challenges for cardiologists and geneticists. However, there is important controversy as to the clinical value, and cost-effectiveness of the use of electrocardiogram as well as of genetic testing to detect these cases. Our review focuses on these current matters of argue.
Keywords: neonates